2019
DOI: 10.1097/cco.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural approaches of cancer pain

Abstract: Purpose of review Pain continues to be a prevalent symptom in cancer patients. Patient's ethnicity may influence the experience of pain with variations in pain outcomes among different ethnic groups. The objective of this thematic review is to investigate the relationship between ethnicity and cancer pain experience, assessment and management. Recent findings Cancer pain is not only a biophysiological construct but is rather a multidimensional concept o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Cancer pain outcomes were associated with psychosocial and cultural factors, which can operate as pain control barriers. 9 According to Barkwell, patients had negative meanings and perceptions about cancer and its pain, originating from their cultural beliefs. 10 Several research examining the cultural and religious origins of cancer patients, the belief in God's will in disease and fatalism, 11 disease as divine punishment, 10 and refusal of treatment due to religious and cultural beliefs 12 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer pain outcomes were associated with psychosocial and cultural factors, which can operate as pain control barriers. 9 According to Barkwell, patients had negative meanings and perceptions about cancer and its pain, originating from their cultural beliefs. 10 Several research examining the cultural and religious origins of cancer patients, the belief in God's will in disease and fatalism, 11 disease as divine punishment, 10 and refusal of treatment due to religious and cultural beliefs 12 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial because pain is highly influenced by the sociocultural context, and a different cultural makeup will affect the way care is delivered to patients with cancer pain. 9 A recently published study by Yu et al 10 investigated knowledge and attitudes among Chinese oncology nurses with regard to cancer pain management. However, in their study, the survey was administered during an education course on cancer symptom management; thus, the motivation and knowledge levels of participating nurses may differ from those of nurses working in cancer wards.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial because pain is highly influenced by the sociocultural context, and a different cultural makeup will affect the way care is delivered to patients with cancer pain. 9 A recently published study by Yu et al. 10 investigated knowledge and attitudes among Chinese oncology nurses with regard to cancer pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer pain is caused by cancer patients' suffering from disease and pain, which makes them prone to bad moods and leads to a decline in self-efficacy, thus affecting the quality of life [44]. In this study, patients mainly reported neuromuscular pain.…”
Section: Discussionmentioning
confidence: 87%